2015
DOI: 10.1016/j.steroids.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of corticosteroids on experimental meningococcal sepsis in mice

Abstract: Neisseria meningitidis is responsible for septicemia and meningitis with high fatality that is associated with an excessive inflammatory reaction particularly with hyperinvasive isolates of the clonal complex ST-11 (cc11). However, anti-inflammatory adjuvant treatment remains controversial and difficult to assess in patients. We addressed this topic in a well-defined experimental meningococcal infection in transgenic mice expressing the human transferrin. Mice were infected by intra-peritoneal challenge with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…The blood was then plated, and bacterial count was determined after overnight incubation at 37°C with 5% CO 2 . Cutaneous temperature was measured using an infrared thermometer (Bioseb) before infection and at 3 h and 24 h post-infection, and used to follow the clinical status of the mice during infection, as hypothermia has been reported as a sign of severe meningococcal infection in the mouse model [29]. Results were expressed as mean temperature loss in comparison with temperature before infection.…”
Section: Infection In Transgenic Micementioning
confidence: 99%
See 1 more Smart Citation
“…The blood was then plated, and bacterial count was determined after overnight incubation at 37°C with 5% CO 2 . Cutaneous temperature was measured using an infrared thermometer (Bioseb) before infection and at 3 h and 24 h post-infection, and used to follow the clinical status of the mice during infection, as hypothermia has been reported as a sign of severe meningococcal infection in the mouse model [29]. Results were expressed as mean temperature loss in comparison with temperature before infection.…”
Section: Infection In Transgenic Micementioning
confidence: 99%
“…Post-infection with NmW and NmY isolates, blood was collected for analysis of cytokines. The proinflammatory cytokine CXCL1 was chosen as it has previously been shown to clearly and directly reflect the proinflammatory response in this model of systemic meningococcal infection [29]. It is expressed by inflammatory cells such as neutrophils and macrophages, and it has neutrophil chemotactic activity [30].…”
Section: Determination Of Cytokine (Cxcl1) Levelsmentioning
confidence: 99%
“…We have previously emphasized the advantages of in vivo bioluminescent imaging for real-time monitoring of meningococcal infections and their treatment (13,16). This technology is sensitive, rapid, and noninvasive.…”
Section: Discussionmentioning
confidence: 99%
“…Prompt recognition and aggressive early treatment are the only effective measures against IMD ( 3 ). Anti-inflammatory adjunctive treatment remains controversial and difficult to assess in patients, especially when it comes to septicaemia with or without meningitis caused by Neisseria meningitidis ( 4 ). Our earlier study showed that the use of dexamethasone has a limited effect on the outcome of the condition, primarily in re-establishing the functions of the blood–brain barrier in the cases of meningococcal sepsis with meningitis by normalizing the values of CSF sugar in comparison to cases in which no dexamethasone was used ( 5 ).…”
Section: Introductionmentioning
confidence: 99%